Sobre el carácter no empírico de los enunciados de confirmación - Cassini, Alejandro (Revista de Filosofía, 2007)
According to all traditional theories of confirmation, statements such as “E confirms H” (where H is a hypothesis and E is the evidence that supports H) are a priori. Peter Achinstein has recently challenged this orthodox position. He claims that at least some confirmation statements are empirical. In this paper I criticize this thesis. I first show that Achinstein´s arguments are either flawed or inconclusive. I then argue that there are strong reasons to conceive of all confirmation statements as a priori. I conclude that inductive logic, if possible, must be a priori knowledge.